The level of awareness regarding conflict and violence in university students and the affective factors in Turkey - (:unkn) unknown (DRUNPP-SARAJEVO, 2012)
Objective: The study was to investigate the awareness level regarding conflict and violence in nursing and medical faculty students, whom in the future will be providing health care, and thus be in direct contact with human beings. Designs: This study was conducted during 2010-2011 educational year, upon 584 students from Ege University, Nursing and Medical Faculties. Any other sampling method was not used. Students who were at the faculties during the school period and voluntarily accepted to participate in the study constituted the sample group (584). Results: A total of 584 students, 362 (62%) from Nursing Faculty, and 222 (38%) from Medical Faculty, participated in the study. 390 (66.8%), were female, and 194 (33.2%) were male. The age of the participants ranged between 19-30 years old, and the mean age was 22.2. The lowest score in the ACVS was 27, and the highest 135, with a mean of 102.81, which shows that the level of awareness of conflict and violence in nursing and medical faculty students was quite high. The difference in the level of awareness of conflict and violence between female and male students was not statistically significant (t=-0.36; p=.71). The level of awareness of conflict and violence was found to be quite high in both groups. Conclusions: According to the results, it was established that the level of awareness of conflict and violence was higher in nursing faculty students compared to medical faculty students, and in the 22-30 age group compared to 19-21 age group. There was no significant difference in the level of awareness of conflict and violence when compared according to gender. In order to solve conflicts by constructive methods and also prevent violence, it is of utmost importance to establish the level of awareness of conflict and violence in individuals.
Keywords: Conflict; violence; university students